Multi-tissue transcriptomics delineates the diversity of airway T cell functions in asthma - Singhania, A; Wallington, J; Smith, C; Horowitz, D; Staples, K; Howarth, P; Gadola, S; Djukanovic, R; Woelk, C; Hinks, T (American Thoracic Society, 2017)
Asthma arises from the complex interplay of inflammatory pathways in diverse cell types and tissues. We sought to undertake a comprehensive transcriptomic assessment of the epithelium and airway T cells that remain understudied in asthma, and investigate interactions between multiple cells and tissues. Epithelial brushings and flow-sorted CD3+ T cells from sputum and bronchoalveolar lavage were obtained from healthy subjects (N=19) and asthmatic patients (mild, moderate and severe asthma; N=46). Gene expression was assessed using Affymetrix HT HG-U133+ PM GeneChips and results were validated by real-time quantitative PCR. In the epithelium, IL-13 response genes (POSTN, SERPINB2, CLCA1), mast cell mediators (CPA3, TPSAB1), inducible nitric oxide synthase and cystatins (CST1, CST2, CST4) were upregulated in mild asthma but, except for cystatins, were suppressed by corticosteroids in moderate asthma. In severe asthma – with predominantly neutrophilic phenotype – several distinct processes were upregulated including neutrophilia (TCN1, MMP9), mucins and oxidative stress responses. The majority of the disease signature was evident in sputum T cells in severe asthma, where 267 genes were differentially regulated compared to health, highlighting compartmentalisation of inflammation. This signature included IL- 17-inducible chemokines (CXCL1, CXCL2, CXCL3, IL8, CSF3) and chemoattractants for neutrophils (IL8, CCL3, LGALS3), T cells and monocytes. A protein interaction network in severe asthma highlighted signatures of responses to bacterial infections across tissues (CEACAM5, CD14, TLR2) including toll-like receptor signalling. In conclusion, the activation of innate immune pathways in the airways suggests that activated T cells may be driving neutrophilic inflammation and steroid-insensitive IL-17 response in severe asthma.